Scattering of carbon dioxide molecules from Pd(111) surfaces - Schlathölter, T.; Heiland, W. (Surface science, 1995)
Carbon dioxide positive ions and neutral molecules are subject to different charge exchange processes when scattered off clean or potassium-covered Pd(111) surfaces under grazing incidence. The time-of-flight method is a suitable tool to investigate these processes with respect to dissociation and different charge state formation. Using projectiles with primary energies of 250 up to 1500 eV we found not only a strong energy dependence but also a sizeable influence of initial charge state and work function on the molecular survival. In particular, potassium increases the dissociation probability whereas switching from CO + 2 to CO 2 projectiles leads to the opposite effect. Furthermore, in the case of CO 2 on Pd(111) +K we found evidence for the formation of negative molecular ions, which are known to play an important role in dissociative chemisorption.